PENGARUH MENONTON FILM PORNO TERHADAP PRILAKU BERPACARAN REMAJA DI DESA BERINGIN JAYA KECAMATAN SINGINGI HILIR KABUPATEN KUANTAN SINGINGI HILIR - ", Susilowati; ", Nurhamlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to identify adolescents who engage in premarital sexual behavior, identify adolescents who have watched pornographic films either via VCD or the Internet, to determine the forms of premarital sexual behavior committed by adolescents and to analyze the effect of watching porn on premarital sexual behavior in adolescents in The Beringin Jaya Village, Singigi Hilir District, Kuantan Singingi Hilir Regency.The population in this study were teenagers aged 17-22 years and The Beringin Jaya Village, Singigi Hilir District, Kuantan Singingi Hilir Regency with a sample of 73 people taken using proportional sampling technique. The sampling method in this research is primary data and secondary data using a questionnaire. Analysis of the data used is descriptive quantitative analysis. Analysis of influence in this study uses the formula χ ^ 2 (Chi square) with a computerized system using the SPSS 25.0 for windows program. The results showed that adolescents classified as having high pre-marital sexual behavior were the majority of men with 3-4 family members and the majority having a high school education. The majority = those who have high intensity in watching porn are men and the majority have high school education. Forms of premarital sexual behavior by adolescents are classified as holding hands, embracing and cheating. There are some teens who are indicated as having oral sex and have had sex. There is a significant influence between watching porn on dating behavior in adolescents in Beringin Jaya Village, Singingi Hiilir District, Kuantan Singingi Regency. This result is evident from the calculation of chi square obtained sig <0.05 (sig = 0.001). This means that the more often the frequency of watching porn films in adolescents will lead to the higher pre-marital sexual behavior of adolescents and conversely the lower the frequency of watching porn in adolescents will result in lower adolescent premarital sexual behavior. Keywords: Watching, Porn Movies, Dating Behavior, and Teens.